Workable environmentally related energy taxes - Navajas, Fernando Heberto (2012)
We model an energy tax reform process out of a status quo and towards environmentally related excises, distinguishing between uniform and non-uniform tax components, positive and normative tax structures, and adopting a non-Ramsey specification. We implement the model for Argentina, Bolivia and Uruguay and find a rebalancing of fuel taxes, where gasoline and diesel are main drivers. Environmental gains of the reform are significant, while fiscal impacts are positive and large. The tax reform has a positive distributive impact in Uruguay, while large pre-existing price distortions tend to produce negative impacts in Argentina and Bolivia.